Practical lexicography : a reader - Fontenelle, Thierry (Oxford linguistics., 2008)
This reader collects some of the best and most useful work in practical lexicography, focusing on the central issues and hottest topics in the field. An essential resource for all students and scholars of lexicography and lexicology as well as professional lexicographers. - ;This book collects and introduces some of the best and most useful work in practical lexicography. It has been designed as a resource for students and scholars of lexicography and lexicology and to be an essential reference for professional lexicographers. It focusses on central issues in the field and covers topics hotly.